2018
DOI: 10.3389/fpsyg.2018.01824
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight Out of Mind: Perceived Physical Distance Between the Observer and Someone in Pain Shapes Observer’s Neural Empathic Reactions

Abstract: Social and affective relations may shape empathy to others’ affective states. Previous studies also revealed that people tend to form very different mental representations of stimuli on the basis of their physical distance. In this regard, embodied cognition and embodied simulation propose that different physical distances between individuals activate different interpersonal processing modes, such that close physical distance tends to activate the interpersonal processing mode typical of socially and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 96 publications
(152 reference statements)
3
30
0
Order By: Relevance
“…Indeed, previous studies have reported the efficacy of this modality, explaining that it enables psychotherapists and patients in separate locations to see each other and interact in real time (i.e., "synchronously"; see Fletcher et al, 2018;Norwood et al, 2018, for reviews). This finding is also supported by experimental studies showing that the perceived distance between two interacting individuals modulates the empathic reaction between them (Schiano Lomoriello et al, 2018), which is a key ingredient of all psychotherapeutic interventions. 6 Finally, therapists' attitudes and beliefs about telepsychotherapy played a significant role in qualitatively shaping their experiences of online sessions.…”
Section: A B Csupporting
confidence: 56%
“…Indeed, previous studies have reported the efficacy of this modality, explaining that it enables psychotherapists and patients in separate locations to see each other and interact in real time (i.e., "synchronously"; see Fletcher et al, 2018;Norwood et al, 2018, for reviews). This finding is also supported by experimental studies showing that the perceived distance between two interacting individuals modulates the empathic reaction between them (Schiano Lomoriello et al, 2018), which is a key ingredient of all psychotherapeutic interventions. 6 Finally, therapists' attitudes and beliefs about telepsychotherapy played a significant role in qualitatively shaping their experiences of online sessions.…”
Section: A B Csupporting
confidence: 56%
“…Namely, painful faces, compared to neutral faces, have elicited the experience-sharing component of empathy, as reflected by the positive shift of only the relatively early P2 and N2–N3 components time-locked to face onsets. On the other hand, painful contexts elicited the mentalizing component of empathy compared to neutral contexts, as reflected by the positive shift of only the relatively later P3 component time-locked to face-onsets (see also other works from one of the authors and other groups in this field: [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]).…”
Section: Introductionmentioning
confidence: 91%
“…Recent evidence further suggests that proximity modulates empathic processes. Lomoriello et al (2018) measured event-related potentials (ERPs) across fronto-parietal and centro-parietal regions in response to images of neutrally and painfully stimulated faces that appeared either spatially close or distant. Empathy-linked ERP responses across both regions were greater among participants exposed to faces that appeared close, versus those who saw relatively distant faces.…”
Section: Proximitymentioning
confidence: 99%